What is the current role of thoracentesis in severe fetal hydrothorax? Case report - Tipiani Rodríguez, Oswaldo (2022)
Hydrothorax is a primary pleural effusion that occurs during prenatal life (called“primary chylothorax” after birth). In certain cases, this effusion is severe andproduces pulmonary and cardiac compression, and perinatal mortality remains high.Newborns with hydrothorax often require drainage, total parenteral nutrition andspecific medication for their recovery. However, prenatal interventions, mainly withthoraco-amniotic shunts, can improve these results. We report the case of a fetuswith severe hydrothorax who underwent thoracentesis and review the literature onits role in current prenatal management